REKAYASA LALU LINTAS PADA SIMPANG DENGAN PERLINTASAN SEBIDANG (STUDI KASUS: SIMPANG PLANDAAN DAN SIMPANG TOKO CANTIK) (FSTPT Indonesia, 2023)
Tulungagung Regency has an intersection where there is a level crossing at one leg of the intersection, namely the Plandaan intersection and the Toko Cantik intersection. The existence of level crossings causes the performance of these intersections to be not optimal and has an impact on the legs of the intersection. Plandaan Intersection is a signalized intersection with four legs of the intersection located at JPL 250. The value of the degree of saturation at Plandaan Intersection is 0.87, the intersection delay is 58.09 seconds/pcu, and 46.44 meters long queue. Then there is the Toko Cantik intersection, which is an unsignalized intersection which has four legs of the intersection which is 560 meters from the Plandaan intersection. At the Simpang Toko Cantik there is an unofficial level crossing. The value of the degree of saturation of this intersection is 0.79, the delay is 15.43 seconds/pcu, and the queue probability is 26 – 51%. The analytical methods carried out in this study are analysis of intersection performance, segment performance analysis, performance analysis of level crossings, analysis of completeness of signs at level crossings, and recommendations for handling the Plandaan and Toko Cantik intersections. After the analysis is done, the scenario is prepared with the help of the PTV Vissim application. Then from each of these scenarios, scenario 1 was selected as the best scenario. Furthermore, the results of this study can be used as a reference from related parties for evaluating traffic performance. ABSTRAK Kabupaten Tulungagung memiliki simpang yang terdapat perlintasan sebidang pada salah satu kaki simpang, yaitu Simpang Plandaan dan Simpang Toko Cantik. Adanya perlintasan sebidang mengakibatkan kinerja dari simpang - simpang tersebut tidak optimal dan berdampak pada kaki - kaki simpangnya. Simpang Plandaan merupakan simpang bersinyal dengan empat kaki simpang yang terdapat JPL 250. Nilai derajat kejenuhan pada Simpang Plandaan yaitu 0,87, tundaan simpang 58,09 detik/smp, dan antrian sepanjang 46,44 meter. Kemudian terdapat Simpang Toko Cantik merupakan simpang tidak bersinyal yang memiliki empat kaki simpang yang berjarak 560 meter dari Simpang Plandaan. Pada Simpang Toko Cantik terdapat perlintasan sebidang yang tidak resmi. Nilai derajat kejenuhan simpang ini adalah 0,79, tundaan 15,43 detik/smp, dan peluang antrian 26 – 51 %. Metode analisis yang dilakukan dalam penelitian ini yaitu analisis kinerja simpang, analisis kinerja ruas, analisis kinerja perlintasan sebidang, analisis kelengkapan rambu pada perlintasan sebidang, dan rekomendasi penanganan pada Simpang Plandaan dan Simpang Toko Cantik. Setelah dilakukan analisis, maka dilakukan penyusunan skenario dengan bantuan aplikasi PTV Vissim. Kemudian dari setiap skenario tersebut terpilih skenario 1 sebagai skenario terbaik. Selanjutnya hasil penelitian ini dapat digunakan sebagai referensi dari pihak terkait untuk evaluasi kinerja lalu lintas.